Can Australia eliminate TB? Modelling immigration strategies for reaching MDG targets in a low‐transmission setting - Justin T. Denholm; Emma S. McBryde (Australian and New Zealand Journal of Public Health, 2014)
Abstract Background: The 2050 Millennium Development Goals (MDG) for tuberculosis (TB) aim for elimination of TB as a public health issue. We used a mathematical modelling approach to evaluate the feasibility of this target in a low‐prevalence setting with immigration‐related strategies directed at latent tuberculosis. Methods: We used a stochastic individual‐based model to simulate tuberculosis disease among immigrants to Victoria, Australia; a representative low‐transmission setting. A variety of screening and treatment approaches aimed at preventing reactivation of latent infection were applied to evaluate overall tuberculosis incidence reduction and rates of multidrug resistant disease. Results: Without additional intervention, tuberculosis incidence was predicted to reach 34.5 cases/million by 2050. Strategies involving the introduction of an available screening/treatment combination reduced TB incidence to between 16.9–23.8 cases/million, and required screening of 136–427 new arrivals for each case of TB prevented. Limiting screening to higher incidence regions of origin was less effective but more efficient. Conclusions: Public health strategies targeting latent tuberculosis infection in immigrants may substantially reduce tuberculosis incidence in a low prevalence region. However, immigration‐focused strategies cannot achieve the 2050 MDG and alternative or complementary approaches are required.